2018, resumen de un año de gratos recuerdos y éxitos para la OPQ - Chong Cáceres, Miguel Angel; Ortega-San-Martin, Luis (Pontificia Universidad Católica del Perú, 2019)
The XXIII Peruvian Chemistry Olympiad was held in 2018 with a historic record of participants. On the other hand, Peruvian students had an outstanding performance in the events carried out internationally, both in Bratislava and Prague (50th International Olympiad, IChO) and in San Salvador, Republic of El Salvador (23th Iberoamerican Olympiad, OIAQ). For the first time, a Peruvian student won a silver medal at the IChO.

En el 2018 se celebró la XXIII Olimpiada Peruana deQuímica con un record histórico de participantes y los estudiantesperuanos seleccionados en 2017 tuvieron una destacada actuación en los eventos realizados internacionalmente, tanto en Bratislava y Praga (50ª Olimpiada Internacional, IChO) como en San Salvador, República de El Salvador (23ª Olimpiada Iberoamericana, OIAQ). Por primera vez, un estudiante peruano se alzó con una medalla de plata en la IChO.
2018, summary of a year full of pleasant memories and successes for the OPQ
Keywords: III OPQ; 50th IChO; 23ª OIAQ; https://purl.org/pe-repo/ocde/ford#1.04.00